Cosmigraphics picturing space through time - Benson, Michael 1962- (Abrams, 2014)
Selecting artful and profound illustrations and maps, many hidden away in the world's great science libraries and virtually unknown today, Benson chronicles more than 1,000 years of humanity's ever-expanding understanding of the size and shape of space itself. He shows how the invention of the telescope inspired visions of unimaginably distant places and explains why today we turn to supercomputer simulations to reveal deeper truths about space-time